EFEKTIVITAS PASAL 27 PERATURAN PEMERINTAH NOMOR 40 TAHUN 1996 TENTANG HAK GUNA USAHA, HAK GUNA BANGUNAN DAN HAK PAKAI ATAS TANAH DALAM PERSOALAN PERPANJANGAN MASA BERLAKU HAK GUNA BANGUNAN - Carrin Finerly; Mella Ismelina F.R. (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2021)
Holders of land in the form of Building Rights Title may be owned by Indonesian Citizens and legal entities established under Indonesian law and domiciled in Indonesia. The Term of Use of Building Rights Title is granted for the first time for 30 years and may extend to a maximum of 20 years. The extension of the Building Rights set forth in Art 27 paragraph (1) of Government Regulation Number 40 Year 1996 on the Right of Exploitation, the Right of Building and the Right of Use of Land/PP 40/1996 may be filed by the rights holder no later than 2 years before the expiry of the Building Rights Period and in Art 41 of Regulation of State Minister for Agrarian Affairs/Head of the National Land Affairs Agency Number 9 Year 1999 on Procedure for Granting and Nullifying Right to State Land and Management Right may be filed within a period of 2 years prior to the expiry of the Building Rights period. According to lex superior derogate the inferiori principle the application for extension of Building Rights should be made in accordance with Art 27 paragraph (1) of PP 40/1996. Type of research is empirical legal research with data collection techniques by literature study and interviews to the Land Office in Central Jakarta. The conclusion of this paper is that holders of Building Rights whenever can extend their rights and no consequences made to whom filed extensions over the time limit in Art 27 paragraph (1) PP 40/1996.